STRATEGI BIMBINGAN MANASIK HAJI JEMAAH LANJUT USIA: STUDI DI KELOMPOK BIMBINGAN IBADAH HAJI DAN UMRAH (KBIHU) HAJAR ASWAD YOGYAKARTA - Noor Hamid (UIN Sunan Kalijaga, 2023)
Hajj is a spiritual journey to complete the perfection of the pillars of Islam that must be carried out in accordance with the science of Hajj manasik, so it is necessary to provide manasik guidance for all pilgrims, including elderly. This study aims to analyze the strategy of manasik guidance for elderly pilgrims at KBIHU Hajar Aswad Yogyakarta. The research uses a qualitative descriptive method. Data collection techniques with interviews, observation and documentation at KBIHU Hajar Aswad Yogyakarta. The results showed that the need for an elderly Hajj manasik guidance strategy due to a decrease in the ability to live and individual sensitivity, and the manasik guidance strategy for elderly pilgrims at KBIHU Hajar Aswad Yogyakarta by mentors by preparing human resources who have competence, professionalism, mentors to treat elderly pilgrims as their own parents. The results of this research academically will be able to add insight and scientific development, especially in the guidance of Hajj and Umrah rituals.